Changes in Corneal Keratocytes and Collagen Fibrils as an Indicator of Keratoconus Onset: A Preliminary Study Based on OCT Subchannel Images - Frederick H Silver; Dominick Benedetto; Tanmay Deshmukh (Frontiers in Bioscience-Landmark)
Background: Keratoconus (KC) is a corneal disease that causes changes in corneal topography, leading to central/paracentral cone formation, which affects visual acuity. Methods: We studied in vivo optical coherence tomography (OCT) images of normal and KC corneas images. The relative cellular and collagen content in the control and KC human corneas was measured by collecting OCT images and then dividing the images into low (green), medium (blue), and high pixel intensity (red) subchannel images. The green image was used to evaluate the cellular content in the cornea, the blue image presented information on the collagen content, and the red image provided information on both the cellular and collagen contents. Results: These results suggest that the cellular and collagen contents decrease with increased corneal depth in KC, while the collagen content appears to reduce as changes in the keratocyte content occur. Conclusion: This study proposes that using the green, blue, and red subchannel OCT images may be an effective method for detecting KC and other corneal diseases earlier, before observing changes in corneal topography, and that these images can be collected remotely using telemedicine.